Recurrence of Uncomplicated Diverticulitis: A Meta-Analysis - Guhyun Kang; Soomin Son; Young-Min Shin; Jung-Soo Pyo (Medicina, 2022)
Background and objective: This study aimed to investigate the estimated rate and risk of recurrence of uncomplicated diverticulitis (UCD) after the first episode through a meta-analysis. Methods: Eligible studies were searched and reviewed; 27 studies were included in this study. Subgroup analyses were performed, based on lesion location, medical treatment, follow-up period, and study location. Results: The estimated recurrence rate of UCD was 0.129 (95% confidence interval [CI] 0.102–0.162). The recurrence rates of the right-and left-sided colon were 0.092 (95% CI 27.063–0.133) and 0.153 (95% CI 0.104–0.218), respectively. The recurrence rate according to follow-up period was highest in the subgroup 1–2 years, compared with that of other subgroups. The recurrence rate of the Asian subgroup was significantly lower than that of the non-Asian subgroup (0.092, 95% CI 0.064–0.132 vs. 0.147, 95% CI 0.110–0.192; p = 0.043 in the meta-regression test). There were significant correlations between UCD recurrence and older age and higher body temperature. However, UCD recurrence was not significantly correlated with medications, such as antibiotics or anti-inflammatory drugs. Conclusions: In this study, detailed information on estimated recurrence rates of UCD was obtained. In addition, older age and higher body temperature may be risk factors for UCD recurrence after the first episode.